Climate Change Perception, Agricultural Impacts, and Adaptation Strategies: A Case of Palanta, Kalikot, Nepal - Panthi, Tirtha Raj; Thapa, Resham Bahadur; Paudyal, Indra Kumar (Journal of Agriculture and Forestry University, 2025)
Climate change has emerged as a critical challenge for agriculture in Nepal, particularly in mountainous districts like Kalikot where livelihoods are highly climate-sensitive. This study aimed to examine the quantitative relationship between rainfall patterns, temperature changes, and the economic value of agricultural production, while also exploring farmers’ adaptation practices and the role of agriculture in greenhouse gas (GHG) emissions mitigation. A stratified cluster sampling method was employed to select 30 households—10 each from low (1,000 masl), mid (1,700 masl), and high (2,200 masl) altitudes in Palanta, Kalikot—ensuring representation across ecological zones with homogeneous farming systems. Primary data were collected using face-to-face semi-structured questionnaires, complemented by focused group discussions. Multi-criteria analysis was applied to rank existing agricultural practices based on criteria such as net profit, resiliency, GHG emissions, workload on females and children, gender equality, social inclusion, institutional, and technological capacity. The findings revealed an overall economic decline of NPR 2,035.33 per household per annum in major agricultural and livestock components, reflecting a 9.7% reduction in rainfall and a 56.41% increase in the economic value of agricultural components over the past 42 years. Reduced rainfall was associated with decreased crop yields and livestock productivity, resulting in notable household-level economic losses. The study identified five top-ranked climate-smart practices: cultivation of drought-tolerant crops or varieties, promotion of fodder and forage, cultivation of high-yielding crops, beekeeping for forage, and tunnel farming. In conclusion, the research underscores the necessity of precise temporal and spatial understanding of climate-agriculture interactions and highlights the importance of integrating GHG emission considerations into future climate-resilient agricultural strategies.